Comparação entre modelos de análise genômica utilizando dados simulados e dados reais em ovinos - Pires, Michele Porto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In Chapter 2 the objective of the work was to evaluate the quality of the genetic merit of predictions between BLUP and GBLUP methods in the presence of uncertainty in the data. In chapter 3 the objective was to compare the BLUP methods, GBLUP and BAYESR considering whether or not to genotypeenvironment interaction in multi-racial sheep. The data used for the realization of Chapter 2 were simulated with three levels of inaccuracy in phenotypic data, 0%, 25% and 50% in three features with magnitude of heritability of 0.02, 0.15 and 0.30, respectively, the BLUP and GBLUP methodologies were applied this data and their performances were compared. To compare the methodologies the mean square error parameters, prediction error variance, bias, accuracy and selection efficiency were used. Better results were obtained by BLUP method over the GBLUP method. The GBLUP method showed no advantage over the BLUP method, except when the magnitude of heritability was 0.02 and there was no inaccuracy in phenotypic data. For chapter 3 we were used 4,288 phenotypes and genotypes dual-core herds of information (Information Nucleus Flock) coming from the Australian Sheep Cooperative Research Center program (CRC). To access the accuracy of the estimates, cross-validation was used. Methods BLUP, GBLUP and BAYESR, were used to estimate breeding values under two models, univariate, which does not consider the genotype-environment interaction and the bivariate model with the interaction effect is considered. The accuracies of the univariate models ranged from 0.17 to 0.27 for the environment 1 and 0.19 to 0.20 for the environment 2. The accuracies of bivariate models ranging from 0.14 to 0.23 for the environment 1 to the environment and the accuracies were 0.19. There was no benefit from the application of genomic selection on BLUP method in environment 2 for gastrointestinal resistance feature. On the other hand, for the application of 1 atmosphere genomic ...

Para o capítulo 2 o objetivo do trabalho foram avaliar a qualidade das predições de mérito genético entre os métodos BLUP e GBLUP na presença de imprecisão nos dados. Para o capítulo 3 o objetivo do trabalho foi comparar os métodos BLUP, GBLUP e BAYESR considerando ou não a interação genótipoambiente em ovinos multirraciais. Os dados utilizados para a realização do capítulo 2 foram simulados com três níveis de imprecisão nos dados fenotípicos, 0%, 25% e 50% em três características com magnitude de herdabilidade de 0,02, 0,15 e 0,30, respectivamente, as metodologias BLUP e GBLUP foram aplicadas nesse dados e seus desempenhos foram comparados. Para a comparação das metodologias os parâmetros de erro quadrático médio, variância do erro de predição, viés, acurácia e eficiência de seleção foram utilizados. Melhores resultados foram obtidos pelo método BLUP em relação ao método GBLUP. O método GBLUP não apresentou vantagem em relação ao método BLUP, exceto quando a magnitude da herdabilidade foi de 0,02 e não houve imprecisão nos dados fenotípicos. Para o capítulo 3 foram utilizados 4.288 fenótipos e genótipos de dois rebanhos núcleos de informação (Information Nucleus Flock) oriundos do Australian Sheep Cooperative Research Center program (CRC). Para acessar a acurácia das estimativas, foi utilizada a validação cruzada. Os métodos BLUP, GBLUP e BAYESR, foram utilizados para estimar os valores genéticos sob dois modelos, univariado, o qual não considera a interação genótipo-ambiente e o modelo bivariado com o efeito da interação é considerado. As acurácias dos modelos univariados variaram de 0,17 à 0,27 para o ambiente 1 e de 0,19 à 0,20 para o ambiente 2. As acurácias dos modelos bivariados variam de 0,14 à 0,23 para o ambiente 1 e para o ambiente 2 as acurácias foram de 0,19. Não houve benefício da aplicação da seleção genômica sobre o método BLUP no ambiente 2 para...
Keywords: Ovino; Genômica; Melhoramento genetico; Métodos estatísticos; Genetica animal; Genomics